Study on outcome of laparoscopic donor nephrectomy - S. K., Subha Kanesh; P., Govindarajan (International Surgery Journal, 2017)
Background: Laparoscopic donor nephrectomy is being performed in increasing numbers since 1995. Now laparoscopic donor nephrectomy has been accepted as good alternate to open procedure as seen in various other abdominal surgeries. This was the basis of the present study. So, the present study was designed to analyse and compare the outcome of Laparoscopic donor nephrectomy and Open donor nephrectomies. Methods: The prospective and observational study was conducted at Stanley Medical College in Department of Urology in 61 Patients aged between 25-50 years who underwent left donor nephrectomy The Mean operating time, warm ischemic time, blood loss, analgesic requirement and duration of hospital stay were recorded and analysed statistically. Results: Out of 61 donor nephrectomies, 16 kidneys harvested by laparoscopic method with only 2 (12%) conversion to open due bleeding. Mean operating time was 179.9±47.6 minutes. Present study showed mean blood loss of (163±93 ml). Analgesic requirement of the LDN (mean 1.25 days) was significantly lower when compared to open group (mean 3.75 days). The present study shows duration of hospital stay was lower in LDN (mean 5.1days). Conclusions: Laparoscopic donor nephrectomy is an effective, safe and rewarding though it is time consuming and technically challenging. The analgesic requirement, duration of hospital stay and the blood loss were less with the laparoscopic surgery. Results of graft functioning of kidneys in both procedures were equivalent. So laparoscopic donor nephrectomy can be made as the procedure of choice in future.